A Road to the Recognition of Home-Workers: Transformation of POS Production Modes and Roles of Home-workers in Batik Industry in Central Java (Case Study in Cluster Batik in Central Java) - Hunga , Arianti Ina R. (Salasika, 2018)
Home-work (HW) in the putting-out system (POS)-based industry is the real proof of global capitalism existence in domestic space. It utilizes house resources and manipulates the domestic area to keep production costs low in order to compete in the global market. POS and HW become paradoxical as they are widely employed and categorized as strategic commodity production, market their products to the global market, and involve certain skills, creativity and technology. Nevertheless, the facts are obscured from public eyes. Efforts to uncover the obscured facts have been done through POS and HW transformation strategies, which are described in this paper. The paper aims at promoting POS and HW into public areas. The data used were gathered through participatory action research on batik industry based on "putting-out" system in cluster batik in Central Java from gender perspectives. The transformation model was used to promote POS and HW and to seek recognition of the facts that were based on system advantages and capacity enhancement of home-workers while enhancing product values through “fair trade” market. The implemented model has four components, namely: 1) development of innovation and technology that focused on product development, production, and marketing on the alternative market; 2) innovation and technological transfer in product development for better value chain and value added; 3) engineering and strengthening of production institutionalization, which is based on POS clusters; 4) engineering and strengthening of marketing institutionalization of alternative market; and 5) development and strengthening of vocal points that are related to and in support of the implementation. This model gave out positive impact on supporting the implementation of POS and POS roles and promoting this reality. As a model, however, this transformation model needed to be developed that it might be disseminated to a larger scale.